1970
DOI: 10.13057/nusbiosci/n060205
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Phoma sp. isolated from medicinal plants promote the growth of Zea mays

Abstract: Kedar A, Rathod D, Yadav A, Agarkar G, Rai M. 2014. Endophytic Phoma sp. isolated from medicinal plants promote the growth of Zea mays. Nusantara Bioscience 6: 132-139. Fungal endophytes are reported as rich sources of valuable secondary metabolites and could be used as bio-fertilizers. In the present study, we report growth promotion potential of two Phoma species isolated from Tinospora cordifolia and Calotropis procera on maize. The fungal endophytes enhanced growth in inoculated maize plants compared to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Various strains of the genus Phoma have been isolated from several medicinal plants, such as L. divaricata (Bernardi-Wenzel et al, 2010), S. saponaria (García et al, 2012), Arisaema erubescens (Wang et al, 2012), P. hispidum (Orlandelli et al, 2012), Tinospora cordifolia, Calotropis procera (Kedar et al, 2014), and Curcuma longa (Gupta et al, 2016). In the current study, Phoma isolates were only identified in samples of L. divaricata and S. saponaria.…”
Section: Discussionmentioning
confidence: 99%
“…Various strains of the genus Phoma have been isolated from several medicinal plants, such as L. divaricata (Bernardi-Wenzel et al, 2010), S. saponaria (García et al, 2012), Arisaema erubescens (Wang et al, 2012), P. hispidum (Orlandelli et al, 2012), Tinospora cordifolia, Calotropis procera (Kedar et al, 2014), and Curcuma longa (Gupta et al, 2016). In the current study, Phoma isolates were only identified in samples of L. divaricata and S. saponaria.…”
Section: Discussionmentioning
confidence: 99%
“…Some Phoma spp. produce growth promoters like gibberellin and cytokinin (Kedar et al 2014) and volatile compounds like ethanol, 1-butanol, 1-hexane, 2-(p-anisyl)-4-methyl, epibicyclosequiphellandrene, butanoic acid, propanoic acid, hexadecanoic acid, dodecanoic acid, etc. (Strobel et al 2011).…”
Section: Secondary Metabolites Of Endophytic Phomamentioning
confidence: 99%
“…Phoma sp. isolated from Tinospora cordifolia and Calotropis procera induces the growth of Zea mays (Kedar et al 2014), and in rice, it induces seed germination (Khan et al 2016). It has also been found that gibberellic acid-deficient rice cultivar (a dwarf variety of rice) shows an increase in plant length when cultivated with culture filtrate of Phoma TK 2-4 a new strain of Phoma herbarum and Phoma LK-13 from Moringa peregrina (Hamayun et al 2009).…”
Section: Plant Growth Promotionmentioning
confidence: 99%
“…There has been increasing attention of the researchers on endophytes from the plants for their bioactivities including growth promotion. In this context, there are reports of growthpromoting Phoma species from the plants ( Shivanna et al 2005;Hamayun et al 2010;Zhou et al 2014;Kedar et al, 2014), for example, Shivanna et al (2005) reported remarkable growth enhancement in cucumber after treatment with Phoma species. In another experiment, 2020) under creative common licence Kedar et al (2014) isolated two endophytic Phoma species inhabiting Tinospora cordifolia and Calotropis procera and evaluated them on maize for growth promotion.…”
Section: Phoma As Plant Growth Promotermentioning
confidence: 99%
“…In this context, there are reports of growthpromoting Phoma species from the plants ( Shivanna et al 2005;Hamayun et al 2010;Zhou et al 2014;Kedar et al, 2014), for example, Shivanna et al (2005) reported remarkable growth enhancement in cucumber after treatment with Phoma species. In another experiment, 2020) under creative common licence Kedar et al (2014) isolated two endophytic Phoma species inhabiting Tinospora cordifolia and Calotropis procera and evaluated them on maize for growth promotion. The authors reported significant growth promotion of treated plants in terms of shoot and root length and biomass (fresh and dry) as compared to untreated control plants of maize.…”
Section: Phoma As Plant Growth Promotermentioning
confidence: 99%